Comparative study between laparoscopic trans-abdominal preperitoneal and open mesh hernioplasty in repair of non-complicated inguinal hernia - Sherpiny, Waleed Yusif El (International Surgery Journal, 2019)
Background: Inguinal mesh hernioplasty is one of the common procedures performed all over the world. It can be done either through open or laparoscopic techniques. The aim of this study was to compare the outcomes of Lichtenstein tension free hernioplasty versus laparoscopic transabdominal pre-peritoneal (TAPP) mesh repair considering, duration of the surgery, hospital stay, and duration to resume normal activity, degree of postoperative pain, wound infection, recurrence and complications. Methods: Adult patients presented to the general surgical OPD, with the diagnosis of inguinal hernia underwent either Lichtenstein repair or laparoscopic repair by TAPP. Results: Patients in Group A (open-repair) had significantly greater level of local pain during rest and during routine activities than those within Group B (laparoscopic group) during the postoperative period assessed on the visual-analogue scale. Mean operative time for open hernia repair was 43.7 minutes and for laparoscopic hernia repair was 59.03 minutes and the difference were statistically significant (p=0.0001). The mean duration of hospital stay for open hernia repair was 2.16 days and that for laparoscopic hernia repair was 1.08 days with a (p=0.00001) which was statistically significant. The time to resume routine activities was much shorter among Group B patients than patients in Group A. Only one recurrence (3.3%) was seen in Group B after 6 months follow up. Conclusions: It is concluded that laparoscopic TAPP repair of inguinal hernia in adults is safe and preferred operation as compared to open inguinal hernia repair.